UPAYA MENINGKATKAN HASIL BELAJAR IPS MATERI KONFLIK DAN INTEGRASI DALAM KEHIDUPAN SOSIAL MELALUI MODEL DISCOVERY LEARNING PADA PESERTA DIDIK KELAS VIII SMP NEGERI 1 BOROBUDUR - Sri Herlina (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
This study aims to improve social studies learning outcomes, by applying the Discovery Learning Model and to obtain evidence that the Discovery Learning model can improve student learning outcomes in social studies class VIII C SMP Negeri 1 Borobudur Magelang. This research is a class action research (PTK) conducted at SMP Negeri 1 Borobudur, with the research target of teachers and students of class VIII C. Data was collected through non-test and test techniques. The results showed that the application of the Discovery Learning Model succeeded in increasing the activity of students in the classroom and the learning outcomes assessed in cycle I and cycle II increased in accordance with the success criteria of the action. Observed learner activities including discipline, activeness, responsibility, and cooperation also increased. Improved learning outcomes can be obtained from the score obtained before the action was held the average value of 63.50. Standard social studies completeness SMPN 1 Borobudur 75, students who have reached completeness before the action held as many as 5 children (15.63%). In cycle I the average score became 77.31 and students who had reached completeness were 26 children (81.25%). In cycle II the average score was 85.56 the number of students who had reached mastery was 30 children (93.75%). In addition, learning by applying the Discovery Learning Model can change the habits and activities of teachers in teaching, which originally teacher centered turned into student centered. Thus learning research Discovery Learning model can improve learning outcomes social studies proven. There is a match of material in the research and learning situation that continues to improve, so that learning outcomes increased significantly.